Mencari Stanislavski di YouTube: Digital Psychophysical Training dalam Pelatihan Keaktoran Mahasiswa - Ilham Rifandi; Ikhsan Satria Irianto; Pandu Birowo (Dance and Theatre Review, 2026)
Searching for Stanislavski on YouTube: Digital Psychophysical Training in Undergraduate Actor Training. This article examines the transformation of acting pedagogy in the digital era by developing the concept of digital psychophysical training. Drawing on Stanislavski's psychophysical tradition and its development by Zarrilli, this study highlights how performing arts students at ISI Padangpanjang, UNIMED, and UNJA use YouTube and TikTok as their primary medium for learning acting. Through a practitioner research approach enriched with digital ethnography, this study analyzes embodied practices arising from screen-body interactions, content consumption patterns, and students' curatorial strategies in navigating algorithms. The findings indicate that: (1) digital platforms function as alternative learning spaces that fill the gap between formal methodologies and acting practices; (2) the process of embodiment occurs through repeated viewing, imitation, and visual translation into physical action, forming a “screen-to-body” literacy; (3) students' acting identities are hybrid, combining global techniques with local cultural roots; and (4) platform algorithms act as “invisible teachers” that shape students' learning trajectories. Despite the risks of dependency, distraction, and algorithmic bias, this experience fosters the strengthening of critical literacy in performing arts education. Thus, digital psychophysical training is understood not simply as a substitute for formal learning, but as a new paradigm that revolutionizes contemporary acting pedagogy in Indonesia.Keywords: digital psychophysical training, algorithmic pedagogy, embodied learning